Ecological distribution of stream macroalgal communities from a drainage basin in the Serra da Canastra National Park, Minas Gerais, Southeastern Brazil - Necchi-Júnior, O. [UNESP]; Branco, L. H. Z. [UNESP]; Branco, C. C. Z. (Instituto Internacional de Ecologia, 2003)
Twelve stream segments were sampled four times in 1998-1999 (one sampling per season) in the drainage basin of the upper São Francisco River (19 masculine 45'-21 masculine 25'S, 49 masculine 05'-51 masculine 30'W), situated in Serra da Canastra National Park, at altitudes ranging from 1,175 to 1,400 m. The macroalgae survey resulted in 30 species, with a predominance of Cyanophyta (12 species = 40%) and Chlorophyta (11 species = 36.5%) and a lower proportion of Rhodophyta (seven species = 23.5%). Two species, Klebsormidium rivulare (Chlorophyta) and Kyliniella latvica (Rhodophyta), were new records for Brazil. Capsosira sp. and Stigonema sp. (Cyanophyta) and the Chantransia stage of Batrachospermum (Rhodophyta) were the most widespread macroalgae, occurring in six sampling sites, whereas 11 species were found at only one site. The proportion of macroalgal morphological types were as follows: mats (33%), free filaments (27%), gelatinous filaments (27%), crusts (7%), tufts (3%), and gelatinous colonies (3%). The flora revealed few species in common (4%-8%) with stream macroalgae from other Brazilian regions. The macroalgal communities proved to have species richness values close to the highest values reported in previous studies. The patterns typical for stream macroalgal communities (patchy distribution and dominance of few species) were also found in this basin. However, the stream variables most influential in macroalgal distribution in this study (rocky substratum, low pH, high COD, water color, and current velocity) were essentially the same that best describe the limnological characteristics of this lotic ecosystem. In addition, this combination of variables differed sharply from results of previous studies in other Brazilian stream ecosystems.

Doze segmentos de riachos foram amostrados quatro vezes em 1998-1999 (uma amostragem em cada estação) na bacia de drenagem do alto rio São Francisco (19o45’-21o25’S, 49o05’-51o30’W), situado no Parque Nacional da Serra da Canastra, em altitudes de 1.175 a 1.400 m. O levantamento das macroalgas resultou em 30 espécies, com predominância de Cyanophyta (12 espécies = 40%) e Chlorophyta (11 espécies = 36,5%) e menor proporção de Rhodophyta (sete espécies = 23,5%). Duas espécies, Klebsormidium rivulare (Chlorophyta) e Kyliniella latvica (Rhodophyta), constituem novos registros para o Brasil. Capsosira sp. e Stigonema sp. (Cyanophyta) e o estágio “Chantransia” de Batrachospermum (Rhodophyta) foram as macroalgas mais amplamente distribuídas, ocorrendo em 6 pontos de amostragem, enquanto 11 espécies foram encontradas em apenas um ponto. As proporções de tipos morfológicos de macroalgas foram as seguintes: emaranhado de filamentos (33%), filamentos livres (27%), filamentos gelatinosos (7%), crostas (7%) e tufos e colônias gelatinosas (3%). A flora teve poucas espécies em comum (4%-8%) com macroalgas lóticas de outras regiões brasileiras. As comunidades de macroalgas mostraram-se ricas, com valores de riqueza de espécies próximos aos mais altos anteriormente reportados. Os padrões típicos para comunidades de macroalgas lóticas de distribuição em mosaico e dominância de poucas espécies também foram encontrados nessa bacia. Entretanto, as variáveis ambientais mais influentes sobre a distribuição de macroalgas neste estudo (substrato rochoso, baixos valores de pH e altos de DQO, cor da água e velocidade da correnteza) foram essencialmente as mesmas que melhor descreveram as características limnológicas desse ecossistema lótico. Além disso, essa combinação de variáveis foi nitidamente diferente dos resultados de estudos anteriores em outros ecossistemas lóticos brasileiros.
Ecological distribution of stream macroalgal communities from a drainage basin in the Serra da Canastra National Park, Minas Gerais, Southeastern Brazil
Keywords: Ecological distribution; Macroalgae; Mountain stream; Highland grassland; Distribuição ecológica; Macroalgas; Riacho de montanha; Campo de altitude